Mathematical modeling of gastrointestinal starch digestion-blood glucose-insulin interactions. (August 2022) - Meraz, M.; Vernon-Carter, E.J.; Bello-Perez, L.A.; Alvarez-Ramirez, J.
Highlights: A plug-flow reactor model for chyme transport and absorption in small intestine. Starch hydrolysis described as a multiphase kinetics. Glucose absorption is mostly affected by the velocity of chyme transport. Abstract: A mathematical model for the interaction between digestible starch in the small intestine and blood glucose homeostasis was proposed in this work. The stomach was described as a mixed tank that feeds the chyme into the small intestine. The starch in the small intestine is hydrolyzed by amylolytic enzymes and the behavior is described from a plug flow reactor setup. The starch contained in meals is hydrolyzed to produce glucose and transported through the small intestine wall to the bloodstream via facilitated transport. The minimal three-states Bergman's model was used to describe the regulation of glucose in blood via insulin interactions. The resulting model comprises nonlinear ordinary and partial differential equations, for which finite differences were used for numerical solution. Numerical simulations were used to explore the effect of different parameters, including stomach emptying rate, chyme velocity in the small intestine, digestible starch composition and concentration. The results showed that the starch composition in terms of rapidly and slowly digestible fractions, and the free glucose content in meals play an important role in the postprandial blood and insulin response.